Refrigerants for eutectic refrigerating systems–Experimental results and future consideration - Vaitkus, Liutauras; Prakopavičius, Lukas; Balčius, Algimantas (International journal of refrigeration, 2024)
The new European F-Gas and PFAS Directives threaten to dramatically reduce quotas or even outright ban synthetic refrigerants, and transition to natural refrigerants in the near future seems inevitable. This article examines eutectic refrigerating systems used in low-temperature transport refrigerators for retail distribution considering transition to natural refrigerants. The main limitation for the operation of eutectic systems is the low evaporation pressure, and various designs addressing this limitation were already tried in the last few years during transition from R507A to R452A and other alternatives. In this article 5 systems with R452A, two with R290 and two with R1270 are compared. The greatest effect was demonstrated by addition of roll-bond plates – it reduced the difference between the inside air and evaporation temperatures by about 3 K. However, this solution is not promising with hydrocarbons due to the higher refrigerant charge. All other solutions together give no more effect than roll-bond plates in terms of evaporation temperature at the end of pull-down. Based on experimental results, the prospects of eutectic refrigeration system with natural refrigerants are reviewed. R290 is not suitable for such systems, but R1270 could be used in systems where eutectic plates just need to be crystallized. However, in weight-optimized systems used in refrigerated vans, the evaporation pressure of R1270 would be lower than atmospheric, which is considered unacceptable due to safety requirements. If this provision remains, the eutectic refrigerators with a single-stage vapour compression refrigerating system become impossible, and more complicated cascade system has to be developed. •The subject of research is the refrigerant of transport refrigerators with eutectic system.•Currently used R452A refrigerant becomes impractical due to F-Gas Quota restrictions.•The main limiting factor is the low boiling pressure at the end of the charging cycle.•The future insights are based on performance of 9 systems with R452A, R290 and R1270.•A possible direction is a low charge R1270 eutectic system with vacuum in the evaporator.